Peningkatan Kesadaran Lingkungan Mahasiswa melalui Edukasi Manajemen Pengelolaan Sampah di Tangerang - Adryan Rachman; Prita Karina Diandra; Maulana Malik Muhammad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This community service activity aims to enhance students’ environmental awareness through field-based education on waste management integrated with managerial perspectives. The program is grounded in the increasing challenges of waste accumulation and the gap between environmental knowledge and actual behavior among students. It was conducted at the Environmental Education Depot in Tangerang, involving students from the Food and Beverage Management Program at Universitas Pradita. A participatory experiential learning approach was implemented, consisting of observation, educational sessions, interactive discussions, and hands-on waste sorting practices. This approach enables students to directly engage with real-world environmental issues, fostering deeper understanding and meaningful learning experiences. The results indicate a significant improvement in students’ comprehension of waste classification, processing systems, and sustainable environmental practices. In addition, there was a noticeable increase in environmental awareness and responsibility, reflected in students’ willingness to adopt proper waste management behaviors in their daily lives. From a managerial perspective, participants also developed an understanding of systematic waste management processes, including planning, organizing, implementation, and control. Overall, this program demonstrates that integrating experiential learning with managerial concepts is effective in strengthening environmental awareness, bridging the gap between theory and practice, and promoting sustainable behavior among students.